Thomas Dixon Jr. and the Birth of Modern America - Hall, Randal L., 1971-; Gillespie, Michele (Book collections on Project MUSE., 2006)
"A sweeping yet rigorous analysis of Dixon and his work. The collection approaches the southern intellectual through multiple methodologies--from literary theory and film studies to social history and religious studies. We get an exhaustive yet diverse perspective on Dixon's influence and legacy."--Journal of American HistoryThomas Dixon Jr. (1864-1946), best remembered today as the author of the racist novels that served as the basis for D.W. Griffith's controversial 1915 classic film The Birth of a Nation, also enjoyed great renown in his lifetime as a minister, lecturer, lawyer, and actor. A.